ILRI annual report 2003: innovative partnerships - International Livestock Research Institute (International Livestock Research Institute, 2004)
This annual report addresses the partnerships that have enhanced ILRI's work at national, regional and international levels, highlighting three particularly inspiring ventures - poverty mapping in East Africa, the Crop-Animal Systems Research Network in Southeast Asia, and development of an improved East Coast fever vaccine, which has engaged researchers from three continents. The five research themes into which ILRI restructured its research portfolio are also outlined. These themes are - Targeting Opportunities; Enabling Innovation; Market Opportunities; Biotechnology; and People Livestock and the Environment. Other topics of discussion include - governance, funding, the search for a vaccine, the role of partnership, research outputs on the internet, an interactive regional research and development platform, mapping poor livestock keepers, and ownership. The report ends with a list of ILRI and staff publications, graduate fellows and their publications, staff list, and list of board of trustees.